Shaping the world of work in the digital economy - Degryse, Christophe (Brussels, 2017)
"For better or worse, the digitalisation of the economy has become an unavoidable theme in political and social debates. This new industrial revolution is predicted to disrupt the processes of production, the world of work and society at large. How can we prepare for this and how can we anticipate its effects?